2020
DOI: 10.12659/aot.921529
|View full text |Cite
|
Sign up to set email alerts
|

First Preliminary Experience with Preservation of Liver Grafts from Extended-Criteria Donors by Normothermic Machine Perfusion in Asia

Abstract: Background: Normothermic machine perfusion (NMP) can provide access to evaluate and resuscitate high-risk donor livers before transplantation. The purpose of this study was to determine the efficacy of NMP in preservation and assessment of extended-criteria donor (ECD) livers in China. Case Reports: From September 2018 to March 2019, 4 liver grafts from 3 transplant center defined as ECD were subjected to NMP, and then were transplanted successfully. During perfusion, perfusion parameters such as vascular flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Various authors claim this technology provides “near-physiological” conditions, although the question, what circumstances from organ donation, transport and transplantation are really physiological? appears [ 9 , 10 , 74 ].…”
Section: How Do We Test Viability During Normothermic Machine Livementioning
confidence: 99%
See 3 more Smart Citations
“…Various authors claim this technology provides “near-physiological” conditions, although the question, what circumstances from organ donation, transport and transplantation are really physiological? appears [ 9 , 10 , 74 ].…”
Section: How Do We Test Viability During Normothermic Machine Livementioning
confidence: 99%
“…Stable perfusion flow rates during NMP were therefore suggested by many [ 22 , 59 , 60 ]. A few authors have defined more specific viability criteria with a portal vein and hepatic artery flow above >500 mL/min and >150 mL/min, respectively ( Table 2 ) [ 9 , 57 , 74 ]. Some case series described a reduction in flow rates toward the end of prolonged NMP, a sign of sinusoidal exhaustion and advanced injury [ 12 ].…”
Section: How Do We Test Viability During Normothermic Machine Livementioning
confidence: 99%
See 2 more Smart Citations
“…One of the main advantages of NMP is that the functional status of grafts can be evaluated by measuring liver metabolic indicators such as bile production and liver enzymes before transplantation 54 . The first case of ECD transplantation by NMP in Asia was reported recently 55 . Multicenter randomized controlled trials have shown that NMP can reduce graft injury, prolong organ preservation time and improve organ utilization 9 , 56 .…”
Section: Mechanism Of Machine Perfusionmentioning
confidence: 99%